Sacerdozio e celibato nella Chiesa cattolica (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Alto valore ecclesiale dello status di chierico sposato - 2. L’obbligo del celibato e le eccezioni - 3. Le norme speciali relative al clero cattolico orientale sposato, in Occidente - 4. Le norme speciali relative all’ordinazione di pastori protestati convertitisi al cattolicesimo - 5. La normativa della Chiesa antica - 6. La disciplina delle Chiese ortodosse.Priesthood and celibacy in the Catholic Church.ABSTRACT: In this period there is discussion about the possibility of abolishing the obligation of celibacy for the Catholic clergy of Latin rite in order to increase their vocations. Some exceptions to this obligation have already been foreseen by the regulations of previous Roman popes for specific cases, aimed at promoting the conversion of Protestant pastors to Catholicism. Canon 373 of the Code of Law of the Eastern Churches states that "must be held in honor the status of clerics united in marriage sanctioned over the centuries by the practice of the early Church and the Eastern Churches", opening up to a re-evaluation of the uxorato clergy. This study aims to recall what is happening today in Eastern Catholic Churches, the exceptions made against Protestant pastors in the Latin Church, as well as the legislation in force in the ancient church, maintained, in substance, in the Orthodox Churches.